In-utero transfer of decidualized endometrial stromal cells increases the frequency of regulatory T cells and normalizes the abortion rate in the CBA/J × DBA/2 abortion model - Zarnani, Kayhan; Zarnani, Kimia; Maslehat-Lay, Nasim; Zeynali, Bahman; Vafaei, Sedigheh; Shokri, Mohammad-Reza; Vanaki, Negar; Soltanghoraee, Haleh; Mirzadegan, Ebrahim; Edalatkhah, Haleh; Naderi, Mohammad-Mehdi; Sarvari, Ali; et al. (Frontiers in Immunology, 2024)
Introduction Failure to adequate decidualization leads to adverse pregnancy outcomes including pregnancy loss. Although there are plenty of reports underscoring immune dysfunction as the main cause of abortion in CBA/J females mated with DBA/2 males (CBA/J × DBA/2), little is known about the potential role of impaired endometrial decidualization. Methods Endometrial stromal cells (ESCs) from CBA/J mice were in-vitro decidualized, and the proteome profile of the secretome was investigated by membrane-based array. CBA/J mice were perfused In-utero with either decidualized ESCs (C×D/D), undecidualized ESCs (C×D/ND), or PBS (C×D/P) 12 days before mating with DBA/2 males. Control mice were not manipulated and were mated with male DBA/2 (C×D) or Balb/c (C×B) mice. On day 13.5 of pregnancy, reproductive parameters were measured. In-vivo tracking of EdU-labeled ESCs was performed using fluorescence microscopy. The frequency of regulatory T cells (Tregs) in paraaortic/renal and inguinal lymph nodes was measured by flow cytometry. The proliferation of pregnant CBA/J splenocytes in response to stimulation with DBA/2 splenocytes was assessed by 5,6-carboxyfluorescein diacetate succinimidyl ester (CFSE) flow cytometry. Results In C×D/D mice, the resorption rate was reduced to match that seen in the C×B group. Intrauterine perfused ESCs appeared in uterine stroma after 2 days, which remained there for at least 12 days. There was no difference in the number of implantation sites and embryo weight across all groups. The frequency of Tregs in the inguinal lymph nodes was similar across all groups, but it increased in the paraaortic/renal lymph nodes of C×D/D mice to the level found in C×B mice. No significant changes were observed in the proliferation of splenocytes from pregnant C×D/D compared to those of the C×D group in response to stimulation with DBA/2 splenocytes. Decidualization of ESCs was associated with a profound alteration in ESC secretome exemplified by alteration in proteins involved in extracellular matrix (ECM) remodeling, response to inflammation, senescence, and immune cell trafficking. Discussion Our results showed that the deficiency of Tregs is not the primary driver of abortion in the CBA/J × DBA/2 model and provided evidence that impaired endometrial decidualization probably triggers endometrial immune dysfunction and abortion in this model.